2018
DOI: 10.1002/nau.23716
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to assist uptake of pelvic floor muscle training for people with urinary incontinence: A clinician viewpoint

Abstract: Clinicians who use pelvic floor muscle training to treat urinary incontinence advised can benefit from accessing explicit details of interventions tested in research and reported as effective. They viewed tailoring therapy to individual goals and the use of verbal prompts and visualization cues as important engagement strategies for effective exercise performance. Explicit reporting could be facilitated by using an exercise guideline template, such as the Consensus on Exercise Reporting Template (CERT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
(111 reference statements)
1
12
0
Order By: Relevance
“…Authors often mentioned their effectiveness to alleviate UI symptoms without explaining the reasoning behind this efficacy, which may reflect an overall lack of understanding of the pathophysiology of UI in women as well as the mechanism of action of PFMT. Tailoring and modification: Tailoring of the exercise intervention was consistently omitted and should be clearly explained; this includes tailoring protocols and rules for intervention modifications and progressions. While most clinicians in pelvic health think individualization and tailoring of exercise prescription parameters for their patients is essential, the majority of studies appeared to include generic protocols involving maximal effort PFM contractions performed daily for a period of between 8 and 12 weeks (eg, three sets of 10 repetitions per day). When tailoring an exercise program, it is important to understand the circumstances around each woman's leakage to adjust her exercises and, possibly, achieve better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Authors often mentioned their effectiveness to alleviate UI symptoms without explaining the reasoning behind this efficacy, which may reflect an overall lack of understanding of the pathophysiology of UI in women as well as the mechanism of action of PFMT. Tailoring and modification: Tailoring of the exercise intervention was consistently omitted and should be clearly explained; this includes tailoring protocols and rules for intervention modifications and progressions. While most clinicians in pelvic health think individualization and tailoring of exercise prescription parameters for their patients is essential, the majority of studies appeared to include generic protocols involving maximal effort PFM contractions performed daily for a period of between 8 and 12 weeks (eg, three sets of 10 repetitions per day). When tailoring an exercise program, it is important to understand the circumstances around each woman's leakage to adjust her exercises and, possibly, achieve better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…All the physiotherapists described the need for an individual training program tailored to the needs of each woman. They reported that patients have different goals and motivations . It is also possible that patients have different characteristics and require different rehabilitation programs.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, women reported more improvement when they received more health professional contact. 45 Slade et al 46 were interested in the experiences of clinicians who use PMFT. All the physiotherapists described the need for an individual training program tailored to the needs of each woman.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The importance of selecting the right treatment for the right patient has been widely acknowledged in the incontinence literature. [21][22][23] Lack of careful consideration on appropriate patient selection for surgery may lead to complications and poor outcomes, 24 which have resulted in the development of evidence-informed algorithms for best practice management. 25 The GPAS pathway not only has the potential to reduce the number of review appointments required before conversion to surgery but also ensured that the patients who were accessing this management option were the most appropriate candidates with a greater chance of a successful clinical outcome because of their pre-operative physiotherapy input.…”
Section: Discussionmentioning
confidence: 99%